PENGARUH KOMPETENSI AUDITOR, KEPATUHAN TERHADAP KODE ETIK, DAN SISTEM PENGENDALIAN MUTU TERHADAP EFEKTIVITAS PENDETEKSIAN KECURANGAN OLEH AUDITOR DI KANTOR AKUNTAN PUBLIK WILAYAH JAKARTA SELATAN - Riduan Syah; Slamet Wahyudi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of Auditor Competence, the Code of Ethics for Public Accountants, and the Quality Control System on Fraud Detection by Auditors. This research falls under the category of quantitative research. The data collection method used is primary data through the distribution of questionnaires. The technique applied involves distributing questionnaires to 135 external auditors working at Public Accounting Firms located in South Jakarta. The sampling technique used is judgment sampling. The research data were analyzed using SPSS version 25. The results of the study indicate that, partially, Auditor Competence has a positive and significant effect on Fraud Detection by Auditors, the Code of Ethics for Public Accountants has a positive and significant effect on Fraud Detection by Auditors, and the Quality Control System also has a positive and significant effect on Fraud Detection by Auditors